2021
DOI: 10.1021/acsami.1c12597
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reconstruction of Cobalt Species on Amorphous Cobalt Silicate-Coated Fluorine-Doped Hematite for Efficient Photoelectrochemical Water Oxidation

Abstract: The slow kinetics of photoelectrochemical (PEC) water oxidation reaction is the bottleneck of PEC water splitting. Here, we report a comprehensive method to improve the PEC water oxidation performance of a hematite (α-Fe 2 O 3 ) photoanode, that is, fluorine doping and an ultrathin amorphous cobalt silicate (Co-Sil) oxygen evolution reaction (OER) cocatalyst by photo-assisted electrophoretic deposition (PEPD). Detailed investigations reveal that fluorine doping can reduce the interfacial transfer resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…Futhermore, the double‐layer capacitance ( C dl ) values are obtained by performing cyclic voltammetry (CV) measurements (Figure S8) over an extremely small potential range, thereby approximately evaluating the electrochemically active surface area (ECSA) of the photoanode [19] . As shown in Figure 4c, the Gd−Fe 2 O 3 photoanode possesses increased C dl value (38.0 μF cm −2 ), which is attributed to the modulation of the electronic structure of α‐Fe 2 O 3 by Gd doping, which in turn improves the surface quality of the photoanode [15a] . FeP/Gd−Fe 2 O 3 has a larger C dl value (56.6 μF cm −2 ) than Fe−Pi/Gd−Fe 2 O 3 (49.0 μF cm −2 ), which indicates that the species evolved on the surface of in‐situ generated FeP has more active sites than intentionally loaded Fe−Pi, which is more conducive to water oxidation.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Futhermore, the double‐layer capacitance ( C dl ) values are obtained by performing cyclic voltammetry (CV) measurements (Figure S8) over an extremely small potential range, thereby approximately evaluating the electrochemically active surface area (ECSA) of the photoanode [19] . As shown in Figure 4c, the Gd−Fe 2 O 3 photoanode possesses increased C dl value (38.0 μF cm −2 ), which is attributed to the modulation of the electronic structure of α‐Fe 2 O 3 by Gd doping, which in turn improves the surface quality of the photoanode [15a] . FeP/Gd−Fe 2 O 3 has a larger C dl value (56.6 μF cm −2 ) than Fe−Pi/Gd−Fe 2 O 3 (49.0 μF cm −2 ), which indicates that the species evolved on the surface of in‐situ generated FeP has more active sites than intentionally loaded Fe−Pi, which is more conducive to water oxidation.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, the further increased N D of FeP/Gd−Fe 2 O 3 photoanode can be attributed to the co‐doping of Gd and P. The Gd doping in the bulk phase significantly increases the N D , while the P diffusion on the surface effectively degrades the surface carrier recombination center and increases the N D synergistically. In addition, α‐Fe 2 O 3 , Gd−Fe 2 O 3 , and Fe−Pi/Gd−Fe 2 O 3 exhibit similar flat‐band potential values (≈0.54 V RHE ), while FeP/Gd−Fe 2 O 3 exhibits a negatively shifted flat‐band potential value (≈0.50 V RHE ), indicating that FeP makes the photoanode more band‐bending [15a] . Futhermore, the double‐layer capacitance ( C dl ) values are obtained by performing cyclic voltammetry (CV) measurements (Figure S8) over an extremely small potential range, thereby approximately evaluating the electrochemically active surface area (ECSA) of the photoanode [19] .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In view of the photoanode/electrolyte interface, the carriers may accumulate on the surface to cause serious interface recombination and affect performance due to electron back transfer and sluggish transfer dynamics. [162][163][164][165] Therefore, an intermediate layer is added to promote carrier transport for the water splitting redox reaction. Tang et al [166] found that TiO 2 forced electrons to be transported to the electrolyte interface, causing serious carrier loss.…”
Section: Intermediate Layermentioning
confidence: 99%
“…[5][6][7] However, the PEC property of the α-Fe 2 O 3 photoanode is unsatisfactory in practical application and is affected by the following defects, for instance, slow water oxidation kinetics, serious bulk and surface recombination of electron and hole, and short hole diffusion distance. [8][9][10] Considering the above, the targeted modification of α-Fe 2 O 3 is necessary to increase its PEC activity by: (i) nanoengineering α-Fe 2 O 3 to compensate for the short minority carrier diffusion length by maximizing the semiconductor-electrolyte interface; 11,12 (ii) increasing the electroconductivity by elemental doping (e.g., F, Ti, Ta); 7,13,14 (iii) passivating the surface states by the decoration of a metal oxide transition layer; 15,16 (iv) heterostructure engineering by utilizing the synergistic effects of different semiconductors; 17,18 and (v) loading cocatalyst to improve the water oxidation kinetics. 19 The state-of-the-art cocatalysts mainly include transition metal oxides (CoO X ), 20 hydroxides (Ni(OH) 2 ), 21 oxyhydroxides (FeOOH, NiOOH, InOOH), [21][22][23] and phosphates (CoPi, FeP).…”
Section: Introductionmentioning
confidence: 99%